Varietal Variances in Photosynthesis and Transpiration Rates of Hibiscus Cannabinus L. (Kenaf) - Tahery, Yaghoob (Global Journal of Food and Agribusiness Management, 2024)
Kenaf (HIBISCUS CANNABINUS L.) is one of the important fiber crops next to cotton which is cultivated for its core and bast fibres. For successful commercial cultivation of kenaf, we need to choose the proper variety with most growth rate and biomass content. As growth and biomass production of plant are strictly related to their physiology attribute, to meet this, we measured gas exchange characteristics of three varieties of guantemala 4 (G4), V36 and kohn kaen 6(KK60) within characteristics, we measured within four regular intervals of 30 days. The varieties showed different gas exchange pattern in each stage of their growth. However, results of study showed that, there was no significant difference between these three varieties in terms of their net photosynthesis (Anet) and transpiration rate. Key words:, , ,.